Functional splinting to promote upper limb function in neurological conditions: ‘Keeping the hand in the game’ - Kate Kelly; Rebecca Jeffcott; Susan Jane Hourihan (Advances in Clinical Neuroscience & Rehabilitation)
Neurological conditions frequently affect hand activity impacting on independence in carrying out everyday tasks. Splinting is frequently completed in neurological rehabilitation to promote incorporation of the affected hand into everyday tasks and to prevent disability. Here we consider the evidence base, clinical reasoning, and application for functional splinting.